2006
DOI: 10.3794/ijme.52.106
|View full text |Cite
|
Sign up to set email alerts
|

Reflecting on the 'International Group Working Experience': a study of two MBA programmes

Abstract: This study explores students' experiences of group working in an internationalising MBA context using the research perspectives of postcolonialism (Spivak 1993;Prasad 2003) and critical management education (Reynolds 1997(Reynolds , 1999Currie & Knights 2003). Data are drawn from interviews with 30 full-time MBA students at two leading UK business schools. Students' perceived gains from the international group working experience are identified, as are areas of concern, such as practices of exclusion and domina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…The challenges of social isolation and lack of initiation into local, culturally-based academic discourses for students from countries such as the PRC, Taiwan and Thailand studying in the UK are well documented (e.g., Volet & Ang, 1998;Wu, 2002;Robinson, 2006;Turner, 2006).…”
Section: Key Conceptsmentioning
confidence: 99%
See 2 more Smart Citations
“…The challenges of social isolation and lack of initiation into local, culturally-based academic discourses for students from countries such as the PRC, Taiwan and Thailand studying in the UK are well documented (e.g., Volet & Ang, 1998;Wu, 2002;Robinson, 2006;Turner, 2006).…”
Section: Key Conceptsmentioning
confidence: 99%
“…The internationalisation of UK higher education (HE) and the expansion of both undergraduate and postgraduate programmes for overseas students in UK universities is well-documented (McNamara & Harris 1997;Scott 1998;Robinson 2006). Recruitment practices have become increasingly business-like within the globalised education marketplace as international education has become a "tradeable commodity" (Skilbeck & Connell, 2006, as cited in Wang 2007.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diverse research evidence has been conducted on home and overseas business and management students experiences in the UK, finding numerous tensions, including a lack of group interaction (Volet and Ang, 1998); home students feeling burdened by the needs of overseas students (Cathcart et al, 2006) and overseas students feeling unfamiliar with western modes of teaching (Robinson, 2006). Furnham (2004) recognised that, as well as the 'culture shock' that many overseas students experience upon arrival in the UK, they are also expected to adapt to the norms within the academic environment, including rapidly conforming to the UK HE systems expectations of learning at PG level.…”
Section: Introductionmentioning
confidence: 99%
“…Furnham (2004) recognised that, as well as the 'culture shock' that many overseas students experience upon arrival in the UK, they are also expected to adapt to the norms within the academic environment, including rapidly conforming to the UK HE systems expectations of learning at PG level. For Chinese, Taiwan and Thailand students studying in the UK, there is evidence of social isolation and lack of initiation into local, culturally-based academic norms (e.g., Volet & Ang, 1998;Wu, 2002;Robinson, 2006;Turner, 2006). Furthermore, in a 2003 survey on Business School staff at a British university, Gannon-Leary and Smailes (2004) reported that lecturers believed that international students had a significant impact on their teaching.…”
Section: Introductionmentioning
confidence: 99%